Prevalence of sweetpotato viruses in Acholi sub-region, northern Uganda - Wokoracha, Godfrey; Edema, Hilary; Muhanguzi, Dennis; Echodu, Richard (Current plant biology, 2019)
The purpose of the study was to identify different viruses infecting sweetpotato and the level of co-infection and spatial distribution of the viruses within the Acholi sub-region of northern Uganda. Multiplex PCR was used to screen and determine level of co-infection in 380 sweetpotato plants. The PCR scores were computed to give overall frequency of occurrence of different viruses. The spatial distribution of viruses was represented on an ArcGIS map. Of all screened samples, 24% (92/380) were infected with at least one virus. Sweetpotato feathery mottle virus (65/92), sweetpotato chlorotic fleck virus (17/92) and sweetpotato mild mottle virus (8/92) were the most frequent viruses detected. Of sampled fields, 74% (28/38) had at least one virus-infected sweetpotato plant. The four viruses detected are the major viruses causing significant yield losses in major sweetpotato growing regions of Uganda and East Africa. The findings of limited distribution and low prevalence of the viruses in the region indicate it causes less burden to sweetpotato production in the sub-region compared with other parts of Uganda.
Keywords: Sweetpotato mild mottle virus; Sweetpotato chlorotic fleck virus; Chlorotic fleck virus; Northern Uganda